Improving the operational performance of a wastewater treatment plant by using GPS-X simulations: a case study in northern Taiwan - Kuen-Lin Chen; Ching-Wen Hou; Chen-Wuing Liu; Han-Yi Wang (Sustainable Environment Research)
Abstract Empirically optimizing the design of a wastewater treatment plant to achieve higher efficiencies of pollutant removal is an extremely time-consuming process. Digital model simulations serve as an effective solution to this problem. The current study used the GPS-X simulation software to simulate five scenarios for improving the oxidation ditch treatment process at the Guishan Wastewater Treatment Plant, which was selected as a case study. The simulation results of the five scenarios revealed that Scenario E, involving a simultaneous increase in flow velocity and aeration of oxidation ditch along with returned flow from the secondary sedimentation tank to the anoxic section of the oxidation ditch, resulted in the most significant improvement in the removal efficiencies for ammonia (36 to 95%) and total nitrogen (51 to 86%). Moreover, among the five scenarios, Scenario E had the lowest carbon emissions but achieved the same increases in removal efficiencies for biological oxygen demand, chemical oxygen demand, ammonia, and total nitrogen.